Effect of cyclic substituents on the anti-cancer activity and DNA interaction of ruthenium(II) bis-phenanthroline dipyridoquinoline - Nyong-Bassey, Etubonesi E.; Hicks, Andrew L.; Bergin, Poppy; Tuite, Eimer M.; Kozhevnikov, Valery; Veuger, Stephany (Frontiers in Molecular Biosciences, 2023)
Ruthenium(II) complexes have emerged recently as candidates for anti-cancer therapy, where activity is related to lipohilicity, cellular localization, and specific interactions with biomolecules. In this work, two novel complexes are reported based on the [Ru(phen)2(dipyrido[3,2-f:2',3'-h]quinoxaline]2+ framework. Compared to the parent complex, addition of cyclopentane and cyclohexane rings to the extended ligand substantially increased cytotoxicity towards a number of cancer cell lines, and induced apoptosis. The complexes localize in the nuclei of cancer cells and co-locate with DAPI on DNA. DNA binding studies show that both complexes bind strongly to DNA and one complex intercalates DNA like the parent, whilst the other appears to have multiple modes of interaction. It is likely that their increased lipophilicity is a key factor for increasing their cytotoxicity, rather than their DNA binding mode.